Transforming Traditional Learning Methods in Pesantren: Integrating Technology in Response to Society 5.0 at Pondok Pesantren Khozinatul Ulum Blora - Intania, Naila; Nurcholis, Nanang (Global Educational Research Review, 2024)
Purpose –  This study explores the transformation of traditional learning methods at Pondok Pesantren Khozinatul Ulum Blora in response to the demands of Society 5.0. It investigates how the pesantren integrates modern technology into its educational practices without compromising its traditional identity, aiming to address gaps in existing research regarding the adaptation of pesantren education to contemporary technological advancements. Methods/Design/Approach – The research employs a descriptive qualitative approach, utilizing a case study method to provide an in-depth analysis of the changes occurring in the pesantren. Data were collected through field observations, structured and unstructured interviews with key stakeholders (e.g., foundation leaders, senior teachers, and pesantren administrators), and relevant documentation. The study applied snowball sampling to select participants and used a systematic process for data reduction, presentation, and analysis. Findings – The study found significant transformations in traditional learning methods such as Bandongan and Sorogan through the adoption of digital tools, the introduction of practical skills training relevant to modern times, and the use of social media to reinforce traditional values. These changes have enhanced the accessibility, interactivity, and effectiveness of learning while maintaining the pesantren’s cultural identity. Originality/Value – This research contributes to the understanding of how traditional educational institutions can successfully integrate modern technology, preserving cultural values while meeting the challenges of Society 5.0. It offers a model for other pesantrens and similar institutions seeking to modernize their educational practices. Practical Implications – The findings provide practical insights for pesantrens and traditional educational institutions on effectively incorporating technology into their curricula without losing their cultural essence. The study highlights the importance of leadership, infrastructure support, and ongoing educator training in ensuring successful technology adoption. Keywords Society 5.0, pesantren education, traditional learning methods, technology integration, cultural preservation Paper type Research paper